Pengaruh Penerapan Sistem E-Filing dan Pemahaman Internet Terhadap Kepatuhan Penyampaian Surat Pemberitahuan Tahunan (SPT) Wajib Pajak Orang Pribadi - Wijaya, Rico; Brilliant, Aulia Beatrice; Solikhin, Agus; Priyanto, Angga (Jurnal Akuntansi & Keuangan Unja, 2024)
This study aims to examine the influence of e-Filing system implementation and public understanding of the internet on individual taxpayers' compliance in submitting annual tax returns (SPT). The study focuses on individual taxpayers registered at KPP Pratama Jambi Telanaipura. The sample was selected using a purposive sampling technique, with a total of 100 respondents determined using the Slovin formula. Data were collected through questionnaire distribution and analyzed using the WarpPLS software. The results show that e-Filing and internet literacy have a significant positive effect on individual taxpayer compliance. This study contributes to increasing taxpayer compliance through the optimization of the e-Filing system and internet literacy. Furthermore, the findings serve as an evaluation of e-Filing effectiveness and a basis for service improvements.